Estudio de factibilidad de una línea de negocio en una clínica de especialidades - Bajaña López, Flor Magdalena (2024)
The research deals with a feasibility study for the creation of a clinical laboratory as a new line of business in the Specialty Clinic, because the current problem of the company is based on the fact that its patients have to perform their medical examinations in other institutions, which causes discomfort to the user. Furthermore, the organization has not carried out internal analyzes to know the financial health of the organization and, based on that, carry out an optimal decision-making process. The methodology has a quantitative approach, where the following methods will be considered: inductive and empirical. While the techniques were the survey and documentary analysis, the first applied to the clinic's clients and the documentary review consisted of the review of the financial statements to learn about the company's finances. The results were that the consumer market has a good perception regarding the implementation of a clinical laboratory in the company under study; while the financial analysis showed that the company is profitable but that it has to improve its working capital to avoid problems in meeting financial obligations in the short term. Therefore, the creation of a new line of business is feasible due to the previous studies and analyzes carried out, and due to values reflected in the proposed financial plan.